Effects of continuous off-the-job training in East Germany after unification - Michael Lechner (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
Retraining the labor force to match the demands of a modern economy is an important task during the transition process from a centrally planned to a market economy. This need is particular pressing in East Germany, because the transition process is much faster there than in the rest of Eastern Europe. Therefore, substantial resources are devoted to this purpose. This paper analyses the impact of continuous off-the-job training in East Germany from the point of view of the individuals who were in the labor force before German unification in 1990. It answers questions about the average gains from participating in a specific type of training. Typical outcomes considered to measure these gains are income, employment status, job security and expected career prospects. The methodology used for the empirical evaluation is the potential outcome approach to causality. This approach has received considerable attention in the statistical literature over the last 15 years and it has been recently rediscovered by the econometric literature as well. Here, it is adapted to allow for important permanent and transitory shocks that influence the decision to participate in the training as well as future labor market outcomes. The empirical results are based on the first five waves of the Socio-Economic Pariel (GSOEP)-East (1990-1994). This panel data set has the advantage that the fourth wave contains a special survey on continuous training and that it allows to keep track of individual behaviour on a monthly, respectively yearly, basis. The econometric analysis focuses on off-the-job training courses that began after unification. Although it is obviously too early to evaluate the long-run implications, the results suggest that at least in the short-run there are no positive effects.
Keywords: 330; Berufsbildung; Arbeitsmarktpolitik; Wirtschaftspolitische Wirkungsanalyse; Neue Bundesländer